Family Financial Revolution Through Digital Finance in The Lower Middle-Class Community - Damis, Sariana; AR, Andi; Sofian, Sofian (PT. Maju Malaqbi Makkarana, 2025)
Digital technology has great potential to revolutionize family finance, especially in rural areas such as Watang Kassa Village, Batulappa District, Pinrang Regency. Digital finance provides solutions for families that previously relied on manual financial record-keeping and traditional financial information systems. With digital technology, people can record and monitor their family finances through digital financial platforms, making family financial management more efficient. Research Objectives: (1) To analyze the level of digital financial literacy among low-income communities and identify the factors influencing it. (2) To evaluate the role of digital financial platforms in helping low-income families manage their finances effectively. (3) To identify the challenges faced by low-income communities in accessing and utilizing digital financial services. (4) To assess the impact of using digital financial technology on family financial management and the well-being of low-income communities. This study employs a Participatory Action Research (PAR) approach. Participatory Action Research is a research method that involves the active participation of the community or group being studied throughout the research process, from planning, implementation, and reflection to corrective actions. The research findings indicate that the community lacks sufficient education regarding financial literacy in the use of digital tools for managing family finances. This lack of education poses a significant challenge in adopting digital finance for financial management among low-income communities. However, with the financial revolution, low-income communities have begun to understand the use of digitalization in managing family finances.